Cybersecurity Awareness Model with Methods: Analytical Hierarchy Process and Structural Equation Model - Gardenia, Yulisa; Gani, Alcianno Ghobadi (EAI Endorsed Transactions on Scalable Information Systems, 2024)
This era of revolution has influenced all sectors of society, including education, where technological advancements are now integral to online teaching and learning. However, not everyone fully understands the potential negative impacts of internet usage. The purpose of this research was to investigate and analyze cybersecurity awareness. The study focused on students at Aerospace Air Marshal Suryadarma University. The research employed a quantitative design, either descriptive (where subjects are typically measured once) or experimental (where subjects are measured multiple times). A descriptive study establishes a relationship between variables, while an experimental study determines causation. To analyze the collected data, SEM AMOS was utilized to measure students' awareness of cybersecurity. The study focused on five key areas: (a) regulation, (b) internet usage, (c) password security, (d) data security, and (e) cyberattacks. Based on the research framework and these focus areas, several indicators were developed for the study. The findings concluded that students are aware of cybersecurity issues.
Keywords: Cybersecurity; cybersecurity awareness; structural equation model